2022
DOI: 10.1161/jaha.121.022638
|View full text |Cite|
|
Sign up to set email alerts
|

Ischemic Stroke Severity and Mortality in Patients With and Without Atrial Fibrillation

Abstract: Background Our objective was to investigate stroke severity and subsequent rate of mortality among patients with and without atrial fibrillation (AF). Contemporary data on stroke severity and prognosis in patients with AF are lacking. Methods and Results First‐time ischemic stroke patients from the Danish Stroke Registry (January 2005–December 2016) were included in an observational study. Patients with AF were matched 1:1 by sex, age, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
5
20
0
Order By: Relevance
“…In our study, patients in the AF group were older than those in the SR group. Among patients with AF, those over 74 years of age accounted for the largest proportion, which is similar to the results of other studies [ 16 , 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, patients in the AF group were older than those in the SR group. Among patients with AF, those over 74 years of age accounted for the largest proportion, which is similar to the results of other studies [ 16 , 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…The findings from previous studies have shown that AF is associated with a worse prognosis in patients with ischemic stroke, but the research mainly assessed short-term mortality and reports of stroke recurrence in patients with coexisting AF are rare [ 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients with atrial fibrillation have a higher risk of thrombogenicity associated with larger thrombus formation ( 16 ), diminished cerebral autoregulation resulting in cerebral dysfunction after stroke ( 17 ), poor collateral circulation due to chronic hypoperfusion from cervical atherosclerosis ( 18 , 19 ), and no recanalization after thrombolytic therapy, as old and large thrombi in the left atrium are more resistant to thrombolysis ( 20 ). However, the Danish Stroke Registry found atrial fibrillation was associated with a higher rate of mortality, which is primarily driven by worse stroke severity and not atrial fibrillation itself ( 21 ). On the other hand, the present study found atrial fibrillation was still associated with higher odds of worse outcomes after adjustment for severity of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Data used in this study was obtained from between October 2015 and September 2018. The inclusion criteria were: >18 years or older, diagnosed with acute severe ischemic stroke (defined by an admission NIHSS score of [15][16][17][18][19][20][21][22][23][24], and available stroke outcome data. Patients with incomplete data were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…middle cerebral artery) resulting in major ischaemic regions, which together with the impaired collateral flow seen in patients with AF, may lead to serious disability and death. 2,3 Endovascular thrombectomy (EVT) has been shown to improve clinical outcomes such as functional independence, successful reperfusion, ICH, and mortality in patients with ischaemic stroke. 4 Furthermore, the evidence derived from observational studies that investigated the effect of AF on people following an ischaemic stroke who underwent EVT has been inconsistent.…”
Section: Introductionmentioning
confidence: 99%